The Influence of Parental Background on the Academic Performance of Junior Secondary School Students in Ankpa LGA of Kogi State - Leonard, Shaibu; Danladi, Momoh; Augustine, Akoji; Christiana, Amaha (American Journal of Education and Learning, 2022)
This study examined the influence of parental background on students’ academic performance in some public secondary schools in Ankpa Local Government Area (LGA) of Kogi state. The purpose of the study was to find out the parental variables that influence students’ academic performance and the extent of their influence on students in schools specifically junior secondary schools. Two research questions guided the study. An ex-post research design was adopted for the study. The Population consisted of 720 respondents. A sample size of 180 staff was randomly selected from 24 public secondary schools. Parental Background and Academic Performance Questionnaire (PBAPQ) was used as an instrument for data collection. The reliability of the instrument was estimated to be 0.82. Mean and standard deviation was used to analyze the data collected for the study. The results revealed that parental socioeconomic level, marital class, income status of parents, size of the family and parental level of education significantly influenced students’ academic performance in schools. Based on the findings, it was recommended that government should introduce programmes that will boost the socio-economic status of the citizenry, re-enact the policy of one wife with few children amongst the citizens of Nigeria, plan remuneration programmes for the family of one wife and four children and expose both parents and students to guidance and counselling unit of the school for proper orientation about the importance of education.